Determinants of Audit Fees in Saudi Arabia - Mohammed A, Alsharari Salman (2009)
The main objective of this research study is to determine the factor that influence audit fees in Saudi Arabia. The research is equally aimed at determining how effective, efficient, prudent, transparency and accountable are the external auditors in Saudi Arabia. This study is aimed at determining the effect of audit fees factors from the viewpoint of the external auditor in Saudi audit firms.